Di Sebalik Isu Natrah, 1950 : Reaksi Pembaca The Straits Times terhadap Tragedi Natrah: Behind the Issue of Natrah, 1950: The Straits Times Reader’s Reaction to the Natrah Tragedy - Abdullah, Dr. Mohd Firdaus; Mohd Noor , Arba’iyah; Mohd Sharif, Mohd Shahrul Azha; Hussain , Norasmahani; Abd Wahab, Norazilawati (Journal of Al-Tamaddun, 2021)
Why did The Straits Times make an effort to give wide coverage about the Natrah tragedy in 1950? Why did this newspaper deploy a strategy to publish letters from readers about Natrah within the specific period of time? What benefit is gained by this newspaper publishing comments and opinions from readers about Natrah? The answer lies in the fact that they were trying to maintain a support from the readers through the report of the Natrah report within the specific period of time. It is known this newspaper managed to spur its own polemic when the publication triggered the Natrah riots and causing casualties among the Muslims. Behind the publication, nevertheless, how reader’s reaction about Natrah? So, in the light of this issue, this article attempts to present how the report about Natrah of The Straits Times managed to influence the thinking and interest of the readers, particulary within the specific period of time. The strength of this article lays on its historical approach applied to interpret the intention and action in the History subject of the Natrah tragedy. This study contributes new findings and novel in its approach which situated from the reaction and thinking of the newspaper’s readers about Natrah.